Unexplained Hypoxemia in School-Age Child: Do Not Forget the Double Superior Vena Cava - Luca Pecoraro; Enrico Boninsegna; Emilio Simonini; Paolo Francia; Stefano Colopi; Angelo Pietrobelli (Children, 2022)
Persistent left superior vena cava (SVC) is a rare congenital malformation of the thoracic venous system. We report a case involving a 7-year-old boy, who was admitted to our CT scanning room because of an incidental discovery of low blood-oxygen levels (90–94% in good health). A persistent left SVC was depicted, with drainage in the left atrium and a resultant right-to-left shunt;right SVC was present, draining to the right atrium. A small bridging vein was depicted. A comprehensive cardiological assessment with echocardiography was performed, but no other anomalies were found. He was successfully treated with a percutaneous endovascular approach and vascular plug deployment. A complete occlusion of the left SVC was obtained, with normalization of the oxygen saturation. Persistent left SVC is a rare vascular anomaly, often incidentally detected. Physicians should be aware because it may have significant clinical implications, especially during catheterization procedures or when associated with other cardiac malformations.